Pengaruh Pelatihan dan Pengembangan Karir Terhadap Produktivitas Kerja Pegawai di Dinas Perhubungan Kota Bima: The Influence of Training and Career Development on Employee Work Productivity at the Bima City Transportation Service - Juari, Putri Sulistiani; Mardian, Irma; Kusumayadi, Firmansyah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to determine and analyze the influence of training and career development on employee work productivity at the Bima City Transportation Service (Dinas Perhubungan). The instrument utilized in this study was a Likert scale questionnaire. The research population consisted of 189 respondents, from which a sample of 34 individuals was selected using purposive sampling techniques. Data collection techniques included observation, questionnaires, and literature review. The data analysis technique employed was multiple linear regression assisted by SPSS for Windows. The results indicate that training has a significant effect on work productivity; however, career development does not have a significant effect on work productivity. The combined contribution of Training and Career Development to Work Productivity is 91.6%. The implication of this study is that the organization cannot merely focus on a single aspect; instead, it is necessary to integrate training programs that enhance employees' technical competencies with clear career development paths to foster long-term motivation and employee loyalty.